Identification of significant geographic clustering of polycythemia vera cases in Montreal, Canada. Issue 22 (5th August 2019) - Le, Michelle; Ghazawi, Feras M.; Rahme, Elham; Alakel, Akram; Netchiporouk, Elena; Savin, Evgeny; Zubarev, Andrei; Glassman, Steven J.; Sasseville, Denis; Popradi, Gizelle; Litvinov, Ivan V.
Abstract : Background: Polycythemia vera (PV) is a chronic myeloproliferative neoplasm associated at times with debilitating symptoms and a significant mortality rate. Understanding the demographics, epidemiology, and geography of this disease may provide further insight into important risk factors associated with its development. The objective of this study was to analyze patient demographics, incidence, and mortality rates, as well as the geographic distribution of PV patients in Canada between 1992 and 2010. Methods: This study was achieved by analyzing the Canadian Cancer Registry, Le Registre Québécois du Cancer, and the Canadian Vital Statistics patient databases. Results: A total of 4645 patients were diagnosed with PV between 1992 and 2010. While the annual incidence rate of this cancer fluctuated in Canada, mortality rate analysis indicated a decreasing trend. Geographically, PV incidence rates were notably elevated in the province of Quebec compared with the Canadian average. Further analysis of high‐incidence forward sortation areas indicated a striking clustering of cases in the H4W region encompassing the Côte‐Saint‐Luc borough of Montreal, with an incidence of 102.97 (95% confidence interval, 75.11‐137.79) cases per million per year, which is >13 times the national average. Conclusion: The residential area of Côte‐Saint‐Luc is an important PV cluster in Canada, with high concentration of retirement homes and geriatric hospices. Also, Jewish residents comprise >60% of the population in this neighborhood. These findings suggest that an older age and, potentially, an inherent genetic predisposition may be implicated in the pathogenesis of this malignancy. This study provides a comprehensive overview of PV burden/geographic distribution of cases in Canada. Abstract : This study provides a comprehensive overview of polycythemia vera burden and geographical distribution in Canada. These findings suggest that older age and, potentially, an inherent genetic predisposition may be implicated in the pathogenesis of this malignancy.